Efficiency of in vitro culture techniques applied to soybean (Glycine max (L.) Merr.) accessions from the VIR collection - E. S. Korshikova; K. M. Ershova; Yu. A. Moksheninova; Yu. V. Ukhatova (Труды по прикладной ботанике, генетике и селекции)
Using a wide range of modern biotechnologies and genetic techniques to study plant germplasm accessions held by VIR makes it possible to procure valuable results, required for the development of new high-yielding cultivars adapted to adverse environmental conditions and possessing specified technological properties, particularly to identify and mark new genes and alleles useful for plant breeding. This research trend is in line with Presidential Decree No. 680 “Concerning the development of genetic technologies in the Russian Federation”. Soybean is among the key crops in agricultural production, but the use of next-generation breeding tools to obtain new soybean cultivars with desired properties is still limited. Successful application of novel methods also requires new approaches to studying soybean accessions, specifically their ability to regenerate and produce calluses for subsequent inclusion in biotechnological programs.Ten soybean accessions of various origin, contrasting in ripening schedules, were selected to study the possibility of effective introduction into in vitro culture and further assessment of their ability to produce calluses and regenerate in in vitro culture. The work included evaluating the effects of different seed sterilization techniques (one-step sterilization, using a commercial bleach, and two-step one, combining the impacts of a chlorine-containing preparation and hydrogen peroxide), types of explants (epicotyls, hypocotyls, cotyledon nodes, and cotyledon leaf segments), and phytohormone composition of nutrient medium: (1) MS + 1.13 mg/L BAP + 0.5 mg/L HA, and (2) MS +1 mg/L BAP + 0.1 mg/L IAA).The assessment results showed that the option of two-step seed sterilization was the most effective for soybean at the stage of in vitro culture initiation, while hypocotyls, epicotyls, and cotyledon nodes had the highest callus formation ability in both types of nutrient media.